Penerapan Desain Perangkap Sampah (Waste Trap) untuk Ekosistem Mangrove Berbasis Pemberdayaan Masyarakat di Kota Ternate - Reyna Ashari; Nurfadhilah Arif; Badrun Ahmad (Universitas Muhammadiyah Palembang, 2024)
The impact of suboptimal waste management caused some people in Gambesi Village, Ternate City choosing to throw their waste into the river. It is eventually carried to the coastal area. Application waste trap technology at the river downstream can prevent waste from being carried to the sea. Therefore, the community service activity team try to apply waste traps in the Gambesi downstream river which is connected to mangrove ecosystem. This activity is carried out in several stages: socialization regarding actual environmental conditions, application of waste trap technology, and mentoring of partner groups. The outputs obtained in this activity are increasing understanding and skills in waste management, installing waste traps in the mangrove ecosystem, and building collaboration with waste management units in Ternate City. The implementation of the socialization has been carried out and attended by 45 participants who are members of Karang Taruna, citizen of Gambesi, and students. The socialization material includes an explanation of waste problems in Ternate City, the impact of waste on health and the environment, the function of waste traps, and methods of application. Participants of the socialization revealed that they were aware of the waste problem in their environment, but only recently learned that waste traps could be one solution to the problem. The installation of waste traps in Gambesi Village was carried out to estuary connected to the sea and the mangrove ecosystem. At that location, 10 traps were installed. Then, the trapped waste wassorted according to its type.